(untitled) (International Conference on Computers in Education, 2013)
The purpose of present study is to develop an automated test assembly tool for Chinese word-segmentation test. Word familiarity and word similarity were both controlled in the experiments. The study examined the effectiveness of automated test by comparing its performance with the traditional test, which was developed by linguistic experts. The results of the present study indicated that the children’s performances on traditional Chinese word-segmentation tests and automated Chinese word-segmentation tests were consistent and comparable. Data collected in different age groups and with larger sample size should be investigated for future research.